2014
DOI: 10.1523/jneurosci.1842-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Upregulation of Presynaptic Kainate Receptors at Immature CA3–CA1 Synapses

Abstract: Presynaptic kainate-type glutamate receptors (KARs) regulate glutamate release probability and short-term plasticity in various areas of the brain. Here we show that long-term depression (LTD) in the area CA1 of neonatal rodent hippocampus is associated with an upregulation of tonic inhibitory KAR activity, which contributes to synaptic depression and causes a pronounced increase in short-term facilitation of transmission. This increased KAR function was mediated by high-affinity receptors and required activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…A handful of reports describe activity‐dependent plasticity of other types of presynaptic receptors. Presynaptic kainate receptors are upregulated during long‐term depression (LTD) at Schaffer collateral synapses, though this was only observed at immature synapses (Clarke, Molchanova, Hirvonen, Taira, & Lauri, ). Presynaptic inhibition through cannabinoid receptors is down regulated at basket cell synapses in the hippocampus during high‐frequency (20 Hz) activity (Földy, Neu, Jones, & Soltesz, ), though this appears to be due to changes in presynaptic voltage‐gated calcium channels rather than the receptor itself.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of reports describe activity‐dependent plasticity of other types of presynaptic receptors. Presynaptic kainate receptors are upregulated during long‐term depression (LTD) at Schaffer collateral synapses, though this was only observed at immature synapses (Clarke, Molchanova, Hirvonen, Taira, & Lauri, ). Presynaptic inhibition through cannabinoid receptors is down regulated at basket cell synapses in the hippocampus during high‐frequency (20 Hz) activity (Földy, Neu, Jones, & Soltesz, ), though this appears to be due to changes in presynaptic voltage‐gated calcium channels rather than the receptor itself.…”
Section: Discussionmentioning
confidence: 99%
“…KARs influence neurite outgrowth and morphological maturation of neurons ( Ibarretxe et al, 2007 ; Joseph et al, 2011 ; Marques et al, 2013 ), regulate mobility of the axonal filopodia ( Chang and De Camilli, 2001 ; Tashiro et al, 2003 ) and mobilization of the synaptic vesicles in the growth cones ( Gelsomino et al, 2013 ). At the stage when a synaptic connection is formed and is already functional, presynaptic KARs are tonically active and inhibit vesicle release; this G-protein dependent signaling regulates the short-term dynamics of transmission ( Lauri et al, 2006 ; Clarke et al, 2014 ) and is suggested to have an important role in activity-dependent fine-tuning of the connectivity in the hippocampus ( Lauri and Taira, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…; Clarke et al . ; Orts‐Del'Immagine & Pugh, ). Many synapses in the central nervous system, including parallel fibres, express a wide range of presynaptic ionotropic and metabotropic receptors; it will be interesting to determine whether other classes of receptors in other brain regions also experience activity‐dependent plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high Cb1 receptor expression at parallel fibre synapses (Herkenham et al 1990;Tsou et al 1998) and that receptor plasticity is generally bidirectional, the physiological mechanisms that up-regulate Cb1 receptor function also remain to be uncovered. The field of presynaptic receptor plasticity is still new, with relatively few examples using physiological stimuli (Lauri et al 2001;Clarke et al 2014;Orts-Del'Immagine & Pugh, 2018). Many synapses in the central nervous system, including parallel fibres, express a wide range of presynaptic ionotropic and metabotropic receptors; it will be interesting to determine whether other classes of receptors in other brain regions also experience activity-dependent plasticity.…”
Section: Discussionmentioning
confidence: 99%